2014
DOI: 10.1155/2014/378738
|View full text |Cite
|
Sign up to set email alerts
|

Sedative Drug Use among King Saud University Medical Students: A Cross-Sectional Sampling Study

Abstract: Introduction. Medical students experience significant psychological stress and are therefore at higher risk of using sedatives. There are currently no studies describing the prevalence of sedative drug use among medical students in Saudi Arabia. The aim of this study was to evaluate the prevalence and factors associated with sedative drug use among medical students in Saudi Arabia. Materials and Methods. A cross-sectional convenience sampling study gathered data by anonymous questionnaire from students enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 37 publications
4
29
4
Order By: Relevance
“…Frequent use of sleeping medication was identified in 8.6% of the participants in the present study, but this proportion is lower than that found in a study involving medical students in Saudi Arabia, which identified that 17% of those students used drugs for sleep induction; this fact indicates the need for early intervention programs targeting poor lifestyle habits. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Frequent use of sleeping medication was identified in 8.6% of the participants in the present study, but this proportion is lower than that found in a study involving medical students in Saudi Arabia, which identified that 17% of those students used drugs for sleep induction; this fact indicates the need for early intervention programs targeting poor lifestyle habits. 21 …”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Frequent use of sleeping medication was identified in 5.5% of the participants in the present study, but this proportion is lower than that found in a study involving medical students in Saudi Arabia, which identified that 17% of those students used drugs for sleep induction; this fact indicates the need for early intervention programs targeting poor lifestyle habits. 35…”
Section: Discussionmentioning
confidence: 99%
“…3.8% of the students in the current study, used pleasureinducing illegal substances at least once (Table 1). The rate of medical students reporting illegal substance use differs from 2.5%-to-7.6% in Turkey (Simsek et al, 2007, Camur et al, 2007, Yalcin et al, 2009, Gorgun aet al, 2010, while it was 17.0% in Saudi Arabia (Al-Sayed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%